PERMASALAHAN DAN TANTANGAN PENINGKATAN INVESTASI INDUSTRI HULU MIGAS - Rastri Paramita (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This study aims to analyze the existing condition of the current upstream oil and gas policy and provide input on how can be more attractive in the future. The method used is qualitative phenomenology. The results of this study are that there are several problems that cause the slow increase in upstream oil and gas investment, including oil and gas is still a source of state revenue, non-conducive regulations, spatial planning and licensing lack of disclosure of geological data related to potential, and less attractive returns for contractors. This study compares fiscal terms with China, India, and Malaysia. The challenges faced by Indonesia's upstream oil and gas include fluctuations in world crude oil prices and supply-demand, geopolitical, and socio-political, meeting the energy transition target towards net zero emission, the implementation of two fiscal regimes that do not support each other, and the absence of asymmetric policies that match the characteristics of the work area. The recommendations are maximized fiscal terms and legal stability that can be adapted to current upstream oil and gas investment, making the two existing fiscal regimes mutually supportive in attracting investors and can be applied differently according to the characteristics of each work area.